Complete vaccination coverage of children born in 2017-2018, living in urban areas of state capitals and in 12 inland cities in Brazil: a population-based survey from a retrospective cohort study - José Cássio de Moraes; Ana Paula França; Ione Aquemi Guibu; Rita Barradas Barata; Carla Magda Allan Santos Domingues; Maria da Gloria Teixeira; Adriana Ilha da Silva; Alberto Novaes Ramos Jr; Ana Paula França; Andrea de Nazaré Marvão Oliveira; Antonio Fernando Boing; Carla Magda Allan Santos Domingues; et al. (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To estimate vaccination coverage in children born between 2017-2018, living in urban areas of state capitals, the Federal District and 12 inland municipalities in Brazil, and to identify associated factors. Methods This was a household survey conducted between 2020-2022, among children up to 24 months old. Vaccination coverage was estimated according to family, maternal and child characteristics. Results Among the 37,801 children in the sample, complete coverage (doses administered) was 60.1% (95%CI 58.6;61.6) and 6.1% (95%CI 5.4;7.0) had not received any vaccines. Coverage was lower among children of mothers with lower level of education (OR = 0.70; 95%CI 0.54;0.90) and in those who experienced delays in receiving any vaccine by 6 months old (OR = 0.28; 95%CI 0.24;0.32). Conclusion Vaccination coverage is below the expected levels. Effective communication strategies are needed to reinforce the importance of routine vaccination, prevent delays and abandonment of the vaccination schedule, in order to recover the high coverage levels achieved in past decades.